Penerapan teknologi budidaya ikan baung (Mystus nemurus CV) di kolam dan keramba - Sukendi Sukendi; Ridwan Manda Putra; Benny Heltonika (Unri Conference Series: Community Engagement, 2019)
The purpose of this community service activity is to provide knowledge and technology to the members of the Sungai Paku Village Natural Fish Farmers Cultivation Group, Kampar Kiri District, Kampar Regency in resolving problems found so far, especially regarding the technology of baung fish farming in ponds and cages. The method used in this activity is the method of lectures, discussions and direct demonstrations. The results of the evaluation of knowledge changes obtained 14 people (70%) have been able to absorb the material provided with the predicate very well, 3 people (15%) can absorb the material given with a good predicate, 2 people (10%) can absorb material given with enough predicate, and only 1 person (5%) can absorb material given with less predicate and not found participants who get predicate less. The results of the skills evaluation showed that the participants of the activity have been able to practice the material provided especially about the manufacture of fish feed (pellets) and how to cope fish diseases in aquaculture. The results of the impact evaluation showed that activity has benefited members of the existing farmer groups, especially in the provision of fish feed (pellets) and management of fish diseases in aquaculture.